Self-diagnosis and self-treatment of malaria in hard-to-reach and mobile populations of the Amazon: results of Malakit, an international multicentric intervention research project. - Maylis Douine; Yann Lambert; Muriel Suzanne Galindo; Louise Mutricy; Alice Sanna; Cassio Peterka; Paola Marchesini; Helene Hiwat; Mathieu Nacher; Antoine Adenis; Magalie Demar; Lise Musset; et al. (Elsevier, 2021)
Background: Illegal gold miners are currently key hosts for malaria in French Guiana (FG), with a risk of emergence of resistance linked to improper use of artemisinin-based combination therapy (ACT). The remoteness of the mines and regulatory issues hinder their access to health care. Methods: A quasi-experimental researched project (Malakit) implemented in FG borders with Brazil and Suriname aimed at determining the effectiveness of distributed kits for self-diagnosis and self-treatment to illegal gold miners, after training, at strategic border staging areas. Evaluation relied on questionnaires at inclusion and follow-up visits, and pre/post intervention surveys. The primary outcome was the proportion of persons reporting a use of certified ACT after a positive malaria diagnosis. The secondary outcomes assessed antimalarial adherence, kit use and impact on malaria epidemiology. Findings: The proportion of patients reporting a use of certified ACT after a positive diagnosis increased after the intervention (OR 1.8, 95%CI [1.1-3.0]). From April 2018 to March 2020, 3,733 persons participated in the intervention. The kit was used correctly by 71.7% [65.8-77.7] of the 223 persons reporting having used a malakit during the follow-up visits. No serious adverse events related to the misuse of malakit have been reported. The intervention appears to have accelerated the decline in malaria incidence in the region by 42.9%. Interpretation: This innovative international project showed that people with low education can correctly self-manage their malaria symptoms. This strategy could be integrated in the malaria control programs of the countries involved and considered in other regions with residual malaria in remote areas. Funding: This project was funded by the European Union, the Global Fund, Brazil MoH, Cayenne Hospital and FG Health Regional Agency. Editor's note: This translation in French was submitted by the authors and we reproduce it as supplied. It has not been peer reviewed. Our editorial processes have only been applied to the original abstract in English, which should serve as reference for this manuscript. The Lancet Group takes a neutral position with respect to territorial claims in published maps and institutional affiliations. Contexte: Les chercheurs d'or illégaux sont actuellement un réservoir clé du paludisme en Guyane, avec un risque d'émergence de résistance lié à une mauvaise utilisation des combinaisons thérapeutiques à base d'artémisinine (ACT). L'isolement de ces sites miniers clandestins et des contraintes règlementaires entravent leur accès aux soins. Méthodes: Un projet de recherche opérationnelle quasi-expérimental (Malakit) a été mis en œuvre aux frontières de la Guyane avec le Brésil et le Suriname. Il visait à déterminer l'efficacité de la distribution de kits d'autodiagnostic et d'autotraitement à des orpailleurs illégaux, après une formation adaptée, dans des zones stratégiques transfrontalières. L'évaluation s'est appuyée sur des questionnaires lors des visites d'inclusion et de suivi, et sur des enquêtes pré/post intervention. L'indicateur principal était la proportion de personnes déclarant avoir utilisé une ACT certifiée après un diagnostic positif de paludisme. Les indicateurs secondaires reposaient sur l'adhérence aux traitements antipaludiques, l'utilisation des kits et l'impact sur l'épidémiologie du paludisme. Résultats: La proportion de patients déclarant une utilisation d'ACT certifiée après un diagnostic positif a augmenté après l'intervention (OR 1,8, 95%CI [1,1-3,0]). D'avril 2018 à mars 2020, 3 733 personnes ont participé à l'intervention. Le kit a été utilisé correctement par 71,7% [65,8-77,7] des 223 personnes revues en visites de suivi ayant déclaré avoir utilisé un malakit. Aucun événement indésirable grave lié à une mauvaise utilisation du malakit n'a été signalé. L'intervention semble avoir accéléré la diminution de l'incidence du paludisme dans la région de 42,9%. Interprétation: Ce projet international innovant a montré que les personnes ayant un faible niveau d'éducation peuvent se prendre en charge par eux-mêmes pour des symptômes de paludisme. Cette stratégie pourrait être intégrée dans les programmes de lutte contre le paludisme des pays impliqués et envisagée dans d'autres régions où du paludisme résiduel persiste dans des zones isolées. Financement: Ce projet a été financé par l'Union Européenne, le Fonds Mondial, le Ministère de la santé du Brésil, le Centre Hospitalier de Cayenne et l'Agence Régionale de Santé de Guyane.